Informatization of construction production organization and operational management - V. V. Sokolnikov; M. V. Molodtsov (Vestnik MGSU)
Introduction. The question of the dependence of the intensity of the operational management of construction production on the organization of interaction between key production executors, services and management of a construction enterprise is considered.Materials and methods. The method of coordinating solutions of current production, support and management tasks based on a unified structure of algorithms of technological processes in the design elevations of the structure, the organization of production activities at the construction site and operational management is presented. The definition of the intensity of operational management as a measure of the effectiveness of the organization of interaction between production, services and management of the enterprise is proposed.Results. The form of analytical continuous, piecewise linear dependence of the intensity of the operational management of the construction process on the coordination of the values of the parameters of the organization of construction production is obtained: its provision with resources, as well as compliance with the requirements of construction control in a changing production situation. The formula for the intensity of operational management of the implementation of the assembly and laying technological process in specific design elevations of the structure within the established timeframes was obtained. The parameters of the mathematical model of the intensity of operational control, as well as the digital interface for its use, are obtained. Boundary values for the variables of the domain of determination of the permissible values of the parameters of the organization of technological processes, providing measures, material supply, as well as a relative scale for the intensity of operational management are obtained. Graphs of changes in the intensity of operational control during the execution of the technical process in the local design elevations of the structure were obtained and analyzed.Conclusions. The conclusion is made about the formation of a unified information environment for the organization of construction production during construction and operational management through compatible algorithms, data structures and AWS interfaces based on a mathematical model that coordinates the algorithms for solving production problems and communication of key performers in terms of the parameters of the organization of construction production and operational management.